The manuscript and its role in the scientific renaissance of the Region of Tedikelt - أحمد بناني (Tamanrasset University Center, 2021)
In this research paper, the researcher tries to find out the role of the manuscript in the scientific renaissance of the Region of Tedkelt, by monitoring the reality of the manuscript in this region, and the role of scientists for those who flocked to the role of the scientific renaissance, the contribution of commercial caravans in the dissemination of science, the stability of manuscripts and delegations of many sciences with them, as well as the riding of pilgrims and its consolidation to meet scientists and discuss the new issues in religion and the worldAnd the role of corners, endowments and lovers of science in the consolidation of the culture of science and scientists and the resurrection of scientific renaissance, and the vaults of manuscripts that whaled the manuscripts of scientists analyzed and traveled, and others collected, monitored and studied their contents, a scientific renaissance formed through a long history charted the path of interconnuality between science and scientists and a static,